Case report: First case of pemetrexed plus cisplatin-induced immune hemolytic anemia in a patient with lung adenocarcinoma - Lu, Hongkai; Wang, Na; Wang, Peng; Zhang, Haolin; Zhao, Ru; Liu, Hongju; He, Xirong; Liu, Zeya; Chang, Yue; Cao, Yongtong; Wang, Shiyao (Frontiers in Medicine, 2022)
Background Drug-induced immune hemolytic anemia (DIIHA) is a rare but potentially life-threatening drug-related complication. There are no previous reports of pemetrexed plus cisplatin as first-line chemotherapy for non-small cell lung cancer, resulting in DIIHA. Case presentation In this report, a patient with advanced-stage lung adenocarcinoma developed severe immune hemolytic anemia 21 days after pemetrexed plus cisplatin chemotherapy. Laboratory findings showed severe hemolysis, including a rapid decrease in hemoglobin (HGB) and an elevated level of reticulocytes (Rets), indirect bilirubin (IBIL), and lactate dehydrogenase (LDH). A workup for the possibility of DIIHA was performed, including a direct antiglobulin test (DAT), a test in the presence of the soluble drug, and a drug-treated red blood cell (RBC) test. It showed a strongly positive (3+) result for anti-C3d but not for anti-immunoglobin G (IgG) in DAT. Enzyme-treated RBCs reacted weakly with the patient's serum and pemetrexed when complement was added. In addition, the patient's serum and normal sera were reactive with cisplatin-treated RBCs. However, eluates from the patient's RBCs and diluted normal sera were non-reactive with cisplatin-coated RBCs. Untreated and enzyme-treated RBCs reacted with the patient's serum in the presence of soluble cisplatin. In vitro serological tests suggested that complement-dependent pemetrexed antibodies and cisplatin-associated non-immunologic protein adsorption (NIPA) might combine to cause immune hemolytic anemia. The patient's anemia gradually recovered when pemetrexed and cisplatin were discontinued. Conclusion This rare case demonstrated that complement-dependent pemetrexed antibodies and cisplatin-associated NIPA might occur simultaneously in a patient with DIIHA.